Immunohistochemical expression of netosis markers (MPO, H2A, H2B) in placenta of RPL women in Basrah Province - Sally Sh. ABED; Wafaa S. SHANI; Dhamya S. ALHAROON (Romanian Journal of Medical Practice)
Background. Recurrent Pregnancy Loss (RPL) is a multifactorial disorder significantly impacting women’s health globally. Emerging research has implicated Neutrophil Extracellular Traps (NETs) in the pathophysiology of RPL, suggesting an immunological underpinning to miscarriage occurrences. Aim. The study aim to evaluate the role and expression of NETosis markers (MPO, histones H2A, H2B) in women with RPL in comparison to pregnant women. Methods. This prospective cohort study, conducted from January 2022 to July 2023, included 30 participants (20 RPL patients and 10 controls) from Al Basrah Maternity and Child Hospital. Immunohistochemical technique were employed to detect Myeloperoxidase and histones in placental samples. Statistical analysis was performed using SPSS, with significance set at p<90.05. Results. Immunohistochemical analysis of placental tissues indicated significant overexpression of Myeloperoxidase (MPO), and histones H2A and H2B, in RPL patients compared to control, emphasizing the potential involvement of NETs in placental pathology associated with miscarriage. The expression levels of MPO were positive in 80% of RPL patients but undetected in control (p = 0.0001). Histone expressions also differed significantly, with H2A detected in 55% of RPL patients compared to none in control (p = 0.001) and H2B in 70% versus 30% (both p <0.001).